2000
DOI: 10.1046/j.1365-2125.2000.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of drug exposure and adverse drug reactions in two Swiss departments of internal medicine

Abstract: Aims To explore drug exposure, frequency of adverse drug reactions (ADRs), types of ADRs, predisposing risk factors and ADR-related excess hospital stay in medical inpatients. Methods Structured data regarding patient characteristics, 'events' (symptoms, laboratory results), diagnoses (ICD10) and drug therapy were collected using a computer-supported data entry system and an interface for data retrieval from electronic patient records. ADR data were collected by 'event monitoring' to minimize possible bias by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
145
2
15

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(182 citation statements)
references
References 10 publications
(14 reference statements)
20
145
2
15
Order By: Relevance
“…Consistent with previous work,[3033] this study identified ADRs to be more common among females (60.7% of the overall ADR-related ED visits) than males. However, females appear to have a lower risk for experiencing severe ADRs.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous work,[3033] this study identified ADRs to be more common among females (60.7% of the overall ADR-related ED visits) than males. However, females appear to have a lower risk for experiencing severe ADRs.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, 62.1% of the studies (18/29) 6,7,8,9,12,13,15,16,19,20,21,22,25,26,27,31,33,34 involved university, academic, or teaching hospitals, i.e., presumably large-scale, high-complexity hospital units.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-eight percent of the studies (14/29) 6,8,9,14,18,19,22,23,24,25,28,29,30,31 used a retrospective approach, i.e., the presence of ADEs was analyzed after the patient was discharged; 48.3% of the studies (14/29) 7,11,12,13,15,16,17,20,21,26,27,32,33,34 used a prospective approach, whereby the ADEs were identified during the hospital stay; and one study 10 was cross-sectional, where ADEs were identified using a survey. Among the studies with a prospective approach, two used retrospective strategies to complement the evaluation, based on an analysis of hospital discharge forms 16,21 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations